Efficiency of microfinance institutions : analysis of Southern African Development Community (SADC) member countries - Agostinho, Elsa Assiaty de L. A. (2021)
Microfinance is seen as an important tool for financial inclusion and the fight against poverty because it has both a social and financial focus. The main objective of this paper is to evaluate the financial and social efficiency of 18 microfinance institutions (MFIs) in the year 2016 from 8 member countries of the Southern African Development Community (SADC). The methodology chosen is the data envelopment analysis (DEA) with variable returns to scale (VRS) using an input-oriented production approach. The results indicate higher scores of financial efficiency than social efficiency. This may suggest that microfinance institutions adopt a more institutionalist approach over the welfarist approach. We also find evidence that providing financial services to women or the entire disadvantaged population is profitable. However, non-bank financial institutions (NBFIs) and non-governmental organizations (NGOs) are more efficient in this regard than credit unions or banks